Response terminated displays unload selective attention - Roper, Zachary J.; Vecera, Shaun P. (Frontiers in Psychology, 2013)
Perceptual load theory successfully replaced the early versus late selection debate by appealing to adaptive control over the efficiency of selective attention. Early selection is observed unless perceptual load (p-Load) is sufficiently low to grant attentional ‘spill-over‘ to task-irrelevant stimuli. Many studies exploring load theory have used limited display durations that perhaps impose artificial limits on encoding processes. We extended the exposure duration in a classic p-Load task to alleviate temporal encoding demands that may otherwise tax mnemonic consolidation processes. If the load effect arises from perceptual demands alone, then freeing-up available mnemonic resources by extending the exposure duration should have little effect. The results of Experiment 1 falsify this prediction. We observed a reliable flanker effect under high p-Load, response-terminated displays. Next, we orthogonally manipulated exposure duration and task-relevance. Counter-intuitively, we found that the likelihood of observing the flanker effect under high p-Load resides with the duration of the task-relevant array, not the flanker itself. We propose that stimulus and encoding demands interact to produce the load effect. Our account clarifies how task parameters differentially impinge upon cognitive processes to produce attentional ‘spill-over’ by appealing to visual short-term memory as an additional processing bottleneck when stimuli are briefly presented.